Immuno-modulation in neonatal sepsis: intravenous immunoglobulin therapy in the prevention and treatment of neonatal sepsis: Is the answer, ‘Yes’, ‘No’, or ‘Don’t know’? (Hematology Meeting Reports, 2009)
Neonatal sepsis remains a major cause of mortality and morbidity in the newborn both in developing and the developed world. This is despite the advances in perinatal and neonatal care and use of very potent antibiotics. This lack of success is in part due to the delayed recognition that disturbed immune homeostasis is a major factor for mortality and morbidity. Unless modalities, which restore immune homeostasis, are used in conjunction with anti-microbials we are unlikely to reduce the unacceptably high mortality and morbidity in neonatal sepsis. Though there are a number of immuno-modulatory therapies available, this paper reviews the evidence on the use of Intravenous Immunoglobulin therapy in the prevention and treatment of neonatal sepsis. This review concludes that whilst there is insufficient evidence for routine use of standard polyvalent Intravenous Immunoglobulin (ivIgG) to prevent neonatal sepsis, there is, compelling evidence that the use of ivIgG as an adjunct would be a beneficial addition to standard treatment of neonatal sepsis. Evidence also suggests that IgM-enriched (ivIgGMA) immunoglobulin may be superior to standard polyvalent ivIgG particularly in Gram-negative infection. Thus, should ivIgG or ivIgGMA be used to prevent neonatal sepsis? The answer is ‘ don’t know’ and to the question should ivIgG or ivIgGMA be used in the treatment of neonatal sepsis the answer is ‘yes’.